Antecedents and consequences of value co-creation in online shopping - Sanaji, Sanaji; Handriana, Tanti; Usman, Indrianawati (BISMA (Bisnis dan Manajemen), 2023)
Customer involvement is necessary for the value co-creation process in online purchases. This study intends to confirm the effect of online shopping experience on customer value co-creation behaviour, represented by participation behaviour and customer citizenship behaviour on repurchase intention and negative electronic word-of-mouth (eWOM). An online survey was conducted to collect data from the customers as respondents. This study used Partial Least Square-Structural Equation Modelling (PLS-SEM) to test the hypotheses. The results show that the data supports four of the seven hypotheses. The online shopping experience positively affects customer participation and citizenship behaviour and then influences repurchase intention, but it does not affect negative eWOM. The results of this study provide an understanding of the importance of a customer experience, customer participation, and customer citizenship behaviours to encourage value co-creation by the customer, which is expected to increase repurchase intention. Previous studies have not linked value co-creation behavior to actual behavioral characteristics. The originality of this study discovers negative eWOM and repurchase factors due to CPB and CCB.